Investigating EFL Learners’ Experiences with Busuu in Supporting Autonomous English Learning - Dwi Safitri; Putu Dian Danayanti Degeng (International Journal of Educational Practice and Policy, 2026)
Many EFL learners experience difficulties initiating English learning due to limited time, financial constraints, and restricted access to formal language courses. This study aimed to investigate EFL learners' experiences of using Busuu to support autonomous English learning and to examine their perceptions of self-determination, self-regulation, and the advantages and disadvantages of the application. The researcher used a Quantitative-Descriptive method by collecting data using questionnaires with Google Form. Data was collected employing five-point Likert Scale questionnaires from 100 EFL learners who were using Busuu for autonomous English learning through a 14-item questionnaire covering four constructs: self-determination, self-regulation, the advantages, and disadvantages of using Busuu. The research questionnaire was distributed through social media such as TikTok and X to all participants who met the criteria. The findings revealed high levels of self-determination (80%) and self-regulation (82%) among the learners. Participants also expressed strong agreement regarding the advantages of Busuu (83%), particularly its gamified activities, structured learning pathways, and opportunities to interact with native speakers, which enhanced motivation and engagement. However, respondents also reported several disadvantages of Busuu (68%), including limited access to premium features and unstable internet connectivity. Overall, the findings indicate that Busuu is a promising mobile-assisted language learning tool for fostering autonomous English learning among EFL learners.